Industrial Agroforestry: A Successful Value Chain Approach in Tamil Nadu - Ramasamy, K. (Indian Farming, 2015)
The TNAU has conceived and designed a value chain model through the NAIP funded project and an institutional mechanism was established to form consortium of stakeholders in public-private partnership and addressing the problems being faced by the stakeholders in a holistic manner thus ensuring a win-win situation for each stakeholder. Thus the current value chain on Industrial Agroforestry is a timely intervention with a unique approach of developing strong linkages among various partners and established a platform for long term sustainability of agroforestry and demonstrated replication potential of this concept across the world.